Quantitative analyses of optically induced birefringence in azo dye containing polymers. (7th October 2019) - Elhani, S; Maouli, I; Refki, S; Halim, M; Hayashi, S; Sekkat, Z
Abstract: We study the steady-state and dynamics of photo-orientation of photoisomerizable azo dyes in films of polymers by using the Kerr gate optical setup, and we show to what extent such experiments can be used to quantify the dyes photoisomerization and photo-orientation. We report on results at different film thicknesses and absorbances and irradiation light intensities. We rationalize the double exponential growth used to describe empirically the onset of photo-induced birefringence in azo-polymers by using the theory of photo-orientation, and we give analytical expressions for the reaction rates, demonstrating a good agreement with experiments, and we show how to extract the trans → cis isomerization quantum yield from birefringence data. We believe that this work will lead to broader studies of the effect of the environment of complex materials on optically reactive molecules.